PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI METODE DISKUSI TUTOR SEBAYA SISWA KELAS XI IPS 2 SEMESTER GENAP DI SMA NEGERI 1 LUMAJANG TAHUN PELAJARAN 2014/2015 - Erfan Syahuri (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2015)
This study aims to find a strategy that is effective and efficient learning in teaching materials Limit Functions Algebra for the students of class XI IPS in SMA Negeri 1 Lumajang by way of peer tutors discussion. Strategies in the classroom action research was conducted through two cycles and in each cycle includes planning, implementation, observation and reflection. Meanwhile, to enable students in this study, researchers used a worksheet given to students in large groups and small groups. Which is the subject of the action research was the students of class XI IPS SMAN 2 Lumajang 1 being the object is learning materials Limit Functions Algebra in Mathematics are taught in a way to enable students who have the potential to serve as peer tutors. From research conducted by examining the initial conditions of students as measured by means of a written test and the results of classroom action research with two cycles seen an increase in the results achieved by students in mastering the material Limit Functions Algebra given. Increasing mastery of this material ranging from cycle I. Values ​​below KKM = 29.4% of the initial conditions being on the conditions in the first cycle after the action on the second cycle Values ​​below KKM = 17.6%. Discussion results from the initial conditions, the cycle I and II can be concluded that the learning outcomes of students has increased as expected, reaching 86.3% in the classical and enter the category "appropriate", and 73.5% above them individually KKM and into the category of "quite appropriate" .with thus be concluded that the method of focus group discussions with peer tutors can improve student learning outcomes though not significantly.